A p57 conditional mutant allele that allows tracking of p57‐expressing cells. Issue 4 (4th April 2017) - Mademtzoglou, Despoina; Alonso‐Martin, Sonia; Chang, Ted Hung‐Tse; Bismuth, Keren; Drayton‐Libotte, Bernadette; Aurade, Frédéric; Relaix, Frédéric
Abstract: p57 Kip2 ( p57 ) is a maternally expressed imprinted gene regulating growth arrest which belongs to the CIP/KIP family of cyclin‐dependent kinase inhibitors. While initially identified as a cell cycle arrest protein through inhibition of cyclin and cyclin‐dependent kinase complexes, p57 activity has also been linked to differentiation, apoptosis, and senescence. In addition, p57 has recently been shown to be involved in tumorigenesis and cell fate decisions in stem cells. Yet, p57 function in adult tissues remains poorly characterized due to the perinatal lethality of p57 knock‐out mice. To analyze p57 tissue‐specific activity, we generated a conditional mouse line ( p57 FL‐ILZ/+ ) by flanking the coding exons 2–3 by LoxP sites. To track p57 ‐expressing or mutant cells, the p57 FL‐ILZ allele also contains an IRES‐linked β‐galactosidase reporter inserted in the 3′ UTR of the gene. Here, we show that the β‐galactosidase reporter expression pattern recapitulates p57 tissue specificity during development and in postnatal mice. Furthermore, we crossed the p57 FL‐ILZ/+ mice with PGK‐Cre mice to generate p57 cKO‐ILZ/+ animals with ubiquitous loss of p57. p57 cKO‐ILZ/+ mice display developmental phenotypes analogous to previously described p57 knock‐outs. Thus, p57 FL‐ILZ/+ is a new genetic tool allowing expression and functional conditional analyses of p57.